Machine Learning-Based Prediction of Divorce Verdicts Using Posita Data and Imbalanced Data Handling: A Case Study in Padang Sidempuan - Rahmadini, Rina; Santoso, Bagus Jati (Indonesian Scientific Journal, 2025)
This study aims to develop a predictive model for divorce verdicts (